The roles and applications of neural stem cells in spinal cord injury repair - Guo, Wen; Zhang, Xindan; Zhai, Jiliang; Xue, Jiajia (Frontiers in Bioengineering and Biotechnology, 2022)
Spinal cord injury (SCI), with no available cures presently, causes severe burden to the patients. In attempts to repair the injured spinal cord, stem cell-based therapies are considered promising, options of which include neural stem cells (NSCs). NSCs are multipotent stem cells that differentiate into neuronal and neuroglial lineages. This feature makes NSCs suitable candidates for the regeneration of the injured spinal cord. Many studies have been conducted to reveal the therapeutic potential of NSCs. Hence, in this review, we intend to discuss how NSCs can help with SCI repair from an integrated view. We will discuss the sources and therapeutic potential of NSCs, as well as representative pre-clinical studies and clinical trials of NSC-based therapies for SCI repair.